Understanding the Factors Influences Users Continuous Intention Towards E-Wallet in Malaysia: Identifying the Gap - Chi Ying, Wong; K.P. Pakir Mohamed, Mohamed Ismail (Research in Management of Technology and Business, 2020)
Digital economy has changed the way people doing business. Cashless transaction via electronic media is the global trend towards achieving cashless society. Malaysia also has such vison. The government rolling out the E-Tunai and E-Penjana cash incentive for the E-wallet user has boosted up the number of E-wallet user with the new sign-up and also increased utilization cashless transaction. The global pandemic, Covid-19, that forced the Malaysian government to implement Movement Control Order (MCO) also affected the consumer ways of making payment. Together with the requirement for social distancing and contactless transaction, the E-wallet payment method is the obvious choice for Malaysia consumer when making purchase. However, the sustainability of the E-wallet user is questionable. There is no guarantee that these new E-wallet users will continuously use E-wallet payment after exhausting the incentives. This research intent to uncover the Malaysian consumer real intention for signing up the E-wallet and identifying the factors that influences the continuous intention to use E-wallet after claiming the government incentives. It is important to understand the users’ involvement and intention toward the usage of E-wallet because by understanding consumer’s behaviour and perception on E-wallet, the government and relevant sectors can develop more effective strategies to sustain and accelerate the growth of E-wallet. The study is vital to determine that the objectives of government e-wallet initiatives and the vision of cashless society in Malaysia are achieved.